INDUCTION OF CARDIOMYOGENIC DIFFERENTIATION OF ADULT BONE MARROW STEM CELLS IN ALBINO RATS BY USING 5-AZACYTIDINE. (Iraqi Journal of Medical Sciences, 2016)
Background: Mesenchymal stem cells have capability for proliferation, self renewing, and differentiation into different types of cells invitro and the medical potential use of these cells is in tissue replacement therapy.Objective: This study aimed to isolate and cultivate mesenchymal stem cells (MSCs) of adult albino rats Rattus rattus norvegicus albinus and enhancement their growth,proliferation and maintainance in active state for several weeks.Methods: The successively passaged cells were exposed on the second day of cultivation to the Minimum essential medium (MEM)with 5-azacytidine at a concentration of 10?mol/L.Results: The results of in vitro study showed that the mesenchymal stem cells showed fibroblast like morphology appearance before 5-azacytidine treatment, but its morphology began to change after 5-azacytidine treatment in about 50% of the adherent cells. These cells were connected with adjoining cells after one week and began to form myotube-like structures at the end of the second week. The immunocytochemical staining demonstrated that the differentiation of mesenchymal stem cells into cardiac-like muscle cells, which was detected by using specific marker (anti-cardiotin),expressed positive response for this marker.Conclusion: Rat mesenchymal stem cells can be extensively expanded in vitro and chemical–induced cardiomyogenic differentiation by 5-azacytidine treatment.Key words: Bone marrow stromal cells; Proliferation; Differentiation; 5-azacytidine; Cell culture
Keywords: Bone marrow stromal cells Proliferation Differentiation 5azacytidine Cell culture